Co‐spray‐drying of a heme iron ingredient to decrease its pro‐oxidant effect in lipid‐containing foods. Issue 2 (21st May 2015) - Alemán, Mercedes; Bou, Ricard; Polo, Javier; Rodríguez, Carmen; Tres, Alba; Codony, Rafael; Guardiola, Francesc
Abstract : Fortification of food products with non‐heme or heme iron is a common strategy to overcome nutritional iron deficiency. Heme iron is highly bioavailable but it promotes oxidation, as do other iron forms. Palm oil is widely used in the formulation of bakery products and chocolate fillings. The work reported here aims to delay the onset of oxidation of a palm oil matrix fortified with heme iron, as a model for bakery products, through the use of ascorbyl palmitate (0 and 400 mg/kg) and the co‐spray‐drying of the heme iron with calcium caseinate in two ratios (heme iron concentrate:caseinate, 2:1 and 1:1, w/w). Primary (peroxide value and lipid hydroperoxide content) and secondary ( p ‐anisidine value and hexanal content) oxidation were measured over one year of storage at room temperature in the dark. The combination of ascorbyl palmitate at 400 mg/kg and the co‐spray‐dried heme iron in a 1:1 ratio was the treatment that best protected iron fortified samples from oxidation during the storage time. Practical applications: Food fortification with iron has been suggested as a good strategy for overcoming iron deficiency. In this study, a heme iron ingredient has been selected due to its higher bioavailability than inorganic iron forms. Nevertheless, as other iron forms, heme iron is a potent pro‐oxidant, which may affect the nutritional value, the sensory properties and shelf life of the fortified product. Thus, in this study the co‐spray‐drying of the heme iron with several coatings was assessed in order to reduce its pro‐oxidant activity. The different heme irons were mixed with palm oil, which is a fat widely used in bakery. The combination of co‐spray‐dried heme iron and ascorbyl palmitate delayed the onset of oxidation, which demonstrates its effectiveness in future iron fortified bakery products. Palm oil is widely used in the formulation of bakery products and chocolate fillings. Therefore, this matrix can be a useful model for iron fortification in bakery products. In a preliminary study with heme iron fortified sunflower oil, the co‐spray‐drying of heme iron with different coating agents delayed the oxidation onset during accelerated storage at 60°C (see the figure).The combination of ascorbyl palmitate and the co‐spray‐drying of heme iron with calcium caseinate at 1:1 ratio (CAS 1:1) prevented oxidation of a heme iron fortified palm oil during storage at room temperature in the dark for one year. Abstract : Palm oil is widely used in the formulation of bakery products and chocolate fillings. Therefore, this matrix can be a useful model for iron fortification in bakery products. In a preliminary study with heme iron fortified sunflower oil, the co‐spray‐drying of heme iron with different coating agents delayed the oxidation onset during accelerated storage at 60°C (see the figure).The combination of ascorbyl palmitate and the co‐spray‐drying of heme iron with calcium caseinate at 1:1 ratio (CAS 1:1) prevented oxidation of a heme iron fortified palm oil during storage at room temperature in the dark for one year.